Network Security Analysis Using PPTP and VPN on the Unmanned Aerial Vehicle PUNA MALE Simulation Prototype - Zen, Bita Parga; Putro, Iwan Nofi Yono; Adhinata, Faisal Dharma (The Republic of Indonesia Defense University, 2026)
Reliable and secure communication is a fundamental requirement for Medium-Altitude Long-Endurance (MALE) Unmanned Aerial Vehicle (UAV) operations, where real-time data transmission must be maintained despite network instability. Internet-Protocol (IP)-based communication networks commonly used in UAV systems are susceptible to delay, jitter, and packet loss, which can degrade mission performance in surveillance and reconnaissance scenarios. This study investigates the capability of a Point-to-Point Tunneling Protocol (PPTP) Virtual Private Network (VPN) to simultaneously enhance communication security and preserve network Quality of Service (QoS) for PUNA MALE UAV communications. A Hardware-in-the-Loop (HIL) simulation environment implemented in GNS3 was developed to emulate realistic operational conditions. Network performance was evaluated using ICMP, TCP, and UDP protocols, with metrics including delay, jitter, and packet loss. Experimental results show that ICMP achieved an average jitter of 0.0879 ms with zero packet loss, while TCP demonstrated superior stability compared to UDP, which exhibited a packet loss rate of 1.9708%. The findings reveal that PPTP VPN deployment can maintain stable QoS performance while providing secure communication channels, indicating its feasibility as a lightweight security solution for UAV communication systems operating in controlled network environments. This work provides empirical evidence supporting the secure integration of VPNs for reliable MALE UAV data communication architectures.